Pengaruh Life Style, Brand Image Dan Kualitas Produk Terhadap Keputusan Pembelian iPhone Di Ngawi - Elsa Dwi Agustina (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2020)
The purpose of this study was to determine the effect of partially and simultaneously life style, brand image and product quality on iPhone purchasing decisions at Ngawi. Respondents in this study were all iPhone buyers in Ngawi. Given the large number of samples and not well recorded, then the sample taken by incidental sampling technique. The number of respondents in this study were 40 iPhone buyers in Ngawi. Data collection techniques using questionnaires and documentation. While the data analysis uses multiple linear regression analysis, analysis of determination and hypothesis testing (t test and F test). The research findings show that (1) there is a partial influence of life style on iPhone purchasing decisions in Ngawi; (2) there is a partial influence of brand image on iPhone purchasing decisions in Ngawi; (3) there is a partial effect of product quality on iPhone purchasing decisions in Ngawi; and (4) there is a simultaneous influence on life style, brand image and product quality on iPhone purchasing decisions at Ngawi.Â Keywordsâ€”: lifestyle; brand image; product quality; purchasing decisions.